Clear, easy, plain, and simple as keywords for text simplification - Sara Vecchiato (Frontiers in Artificial Intelligence, 2022)
In this paper, we distinguish between four interconnected notions that recur in the literature on text simplification: clarity, easiness, plainness, and simplicity. While plain language and easy language have both been the subject of standardization efforts, there are few attempts to define text clarity and text simplicity. Indeed, in the definition of plain language, clarity has been favored at the expense of simplicity but is employed as a self-evident notion. Meanwhile, text simplicity suffers from a negative connotation and is more likely to be defined by its antonym, text complexity. In our analysis, we examine the current definitions of plain language and easy language and discuss common definitions of text clarity and text complexity. We propose a model of text simplification that can clarify the transition from specialized texts to plain language texts, and easy language texts. It is our contention that text simplification should be placed in a more general framework of discursive ergonomics.